2021
DOI: 10.1038/s41531-021-00177-8
|View full text |Cite
|
Sign up to set email alerts
|

Expediting telehealth use in clinical research studies: recommendations for overcoming barriers in North America

Abstract: Despite data supporting the rapid adoption of telehealth in the delivery of clinical care in North America, the implementation of telehealth visits in clinical research studies has faced critical barriers. These challenges include: (1) variations in state licensure requirements for telehealth; (2) disparities in access to telehealth among disadvantaged populations; (3) lack of consistency among individual Investigational Review Boards (IRBs). Each barrier prevents the systematic conversion of research protocol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…Telemedicine could facilitate time-efficient multidisciplinary care, as it has the ability to connect multiple health care professionals simultaneously [ 21 ]. Furthermore, telemedicine has the potential to facilitate cancer survivorship care, pain and symptom management in the palliative care setting, and participation in clinical trials for rural patients [ 22 , 23 , 24 ]. Due to the large rural population in Saskatchewan, telemedicine was incorporated into patients’ care by various disciplines several years prior to the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Telemedicine could facilitate time-efficient multidisciplinary care, as it has the ability to connect multiple health care professionals simultaneously [ 21 ]. Furthermore, telemedicine has the potential to facilitate cancer survivorship care, pain and symptom management in the palliative care setting, and participation in clinical trials for rural patients [ 22 , 23 , 24 ]. Due to the large rural population in Saskatchewan, telemedicine was incorporated into patients’ care by various disciplines several years prior to the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…North American clinicians reported patient resistance to videoconferencing in the early COVID-19 crisis as the second barrier to its implementation, after the lack of access to technology [ 40 ]. It will therefore be critical to ensure that deploying video-based consultations does not create disparities between patients from different socioeconomic backgrounds, not only for their medical care but also for their inclusion into research studies [ 41 ]. Lastly, clinical studies have suggested that telemedicine for PD patients is as effective as in-person care [ [42] , [43] , [44] ].…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Similarly, for research, valid tools that can be applied through telehealth could improve recruitment and retention, reduce costs, and ensure single rater consistency for clinical endpoints. 3 As our screening data suggests, there is also increasing evidence for the ubiquity of home internet and smartphones among the aging population. [29][30][31] There is a growing body of literature supporting the feasibility, validity, and reliability of conducting motor assessments remotely in PD, but the objective assessment of rigidity, postural stability, and overall fall-risk have been considered problematic on standard rating scales without in-person assessment.…”
Section: Discussionmentioning
confidence: 89%